Estimation method for generator spurious synchronization used in mechanical transducer on surface acoustic waves (Visnyk NTUU KPI Seriia - Radiotekhnika Radioaparatobuduvannia, 2013)
Introduction. The mechanical-electric transducer (MET) on surface acoustic waves is (SAW) built on the differentiated scheme. It consists of two SAW generators that operate on similar frequencies. It impairs their metrological characteristics. Requirements for document. Mutual synchronization of generators leads to random fluctuation of the output frequency and the output frequency is not linear. There are schemes and construction to improve performance. However, there is no method that allows objectively to estimate its impact on performance. Methodology of such assessment is proposed in the article. The structure of the materials. The causes of mutual synchronization SAW generators are considered. Reducing methods and evaluation methods and the results of the several types of  converters study are presented. Conclusions. The method of assessment SAW generators spurious synchronization used in mechanical-electric transducer allows objectively to estimate the connection degree by nonlinearity of output frequency.